KORELASI PEMBELAJARAN FLIPPED CLASSROOM DENGAN TAKSONOMI BLOOM - I Putu Suardipa; I Made Sedana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Flipped classroom is recommended learning when the teacher is preparing to carry out synchronous and asynchronous learning activities because of its effectiveness. This effectiveness is obtained because the flipped classroom is supported by four pillars of innovative learning: flexible environment, learning culture, intentional content, and professional educator, based on a constructivist learning approach and the design involved can activate and develop thinking skills in the realm of Bloom's taxonomy. The correlation that appears in the study above gives place to the Flipped classroom by assigning students to know and understand the content of lessons outside the classroom by using higher order thinking skills (HOTs) in Bloom's Taxonomy as a guardian of activities. Bloom's Taxonomy content in the Flipped Classroom model has a reverse direction, in the Flipped Classroom model step by emphasizing on students to create a product first, then students reconstruct understanding by trying to criticize to be evaluated (evaluating) in the application, then look at the details the strengths and weaknesses of the resulting product (analyzing) so that students apply the best working strategy (applying) by gaining new understanding (understanding) and being able to remember all previous learning. After students have